2012
DOI: 10.1186/2045-3701-2-31
|View full text |Cite
|
Sign up to set email alerts
|

Golgi phosphoprotein 2 in physiology and in diseases

Abstract: Golgi phosphoprotein 2 (GOLPH2, also termed GP73 and GOLM1) is a type II transmembrane protein residing in the cis and medial-Golgi cisternae. GOLPH2 is predominantly expressed in the epithelial cells of many human tissues. Under poorly defined circumstances, GOLPH2 can be cleaved and released to the extracellular space. Despite of its relatively “young age” since the first description in 2000, the physiological and pathological roles of GOLPH2 have been the subject that has attracted considerable amount of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
(39 reference statements)
0
32
0
Order By: Relevance
“…GOLM1 has two variants which encode the same protein ( 26 ). Previous studies have demonstrated that the GOLM1 expression is overexpressed in human PCa tissues ( 27 ), HCC ( 28 ), and lung adenocarcinoma ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…GOLM1 has two variants which encode the same protein ( 26 ). Previous studies have demonstrated that the GOLM1 expression is overexpressed in human PCa tissues ( 27 ), HCC ( 28 ), and lung adenocarcinoma ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…GOLPH2 expression is closely correlated with many diseases (Kim et al, 2012), including hepatocellular carcinoma (Riener et al, 2009), kidney cancer , prostate cancer Wei et al, 2008;Laxman et al, 2008;Roobol et al, 2011), seminoma (Fritzsche et al, 2010), lung adenocarcinoma (Zhang et al, 2010), and others. GOLPH expression was significantly higher in the urine of patients with prostate cancer than in normal controls (Laxman et al, 2008;Roobol et al, 2011), and both the mRNA and protein levels of GOLPH2 were significantly higher than in the normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, GOLPH2 is mainly localized in the cis Golgi; however, it can be secreted into the blood through the membrane transport system (Hu et al, 2011). GOLPH2 is a very important biomarker in a variety of diseases (Kim et al, 2012). GOLPH2 was detected in the lesions and sera of patients with liver disease (Riener et al, 2009), and in the lesions of patients with kidney cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis indicated that GOLM1-MAK10 could result in the substitution of the last 25 amino acids of GOLM1 by 26 new amino acids and a new 3' UTR from MAK10 (Figure 5A). This would leave the signal peptide and transmembrane domain of GOLM1 intact [16], hence leading to the secretion of an aberrant fusion protein. To investigate this possibility, we cloned the full length ORF of GOLM1-MAK10 and tagged it with a FLAG sequence (Figure 5B), and transfected it in HEK 293T cells.…”
Section: Resultsmentioning
confidence: 99%